Upaya Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran PjBL pada Mata Pelajaran Sistem Kendali : Penelitian - Dewi Ummu Karima; Hari Putranto; Arif Wicaksono (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to improve student learning achievement in the subject of Control Systems through the  implementation of the Project-Based Learning (PjBL) model in Grade XI Electrical Power Installation  Engineering (TITL) at SMK Nasional Malang. The research used the Classroom Action Research (CAR)  method with the spiral model of Kemmis and McTaggart, consisting of planning, action, observation, and  reflection stages carried out over two cycles. The research subjects were 23 students of Grade XI TITL. Instruments used included cognitive tests, observation sheets, and activity documentation. The results  showed a significant improvement in students' cognitive learning mastery. In the pre-cycle, only 4 students  achieved mastery, which increased to 14 students in the first cycle and reached 23 students in the second  cycle. The implementation of the PjBL model proved effective in enhancing conceptual understanding and  encouraging active student engagement. These findings support the idea that project-based learning enables students to build their knowledge through direct experience in solving contextual problems.